Changing elemental cycles, stoichiometric mismatches, and consequences for pathogens of primary producers. Issue 7 (23rd April 2021) - Frenken, Thijs; Paseka, Rachel; González, Angélica L.; Asik, Lale; Seabloom, Eric W.; White, Lauren A.; Borer, Elizabeth T.; Strauss, Alex T.; Peace, Angela; Van de Waal, Dedmer B.
Abstract : Human‐induced changes in biogeochemical cycles alter the availability of carbon (C), nitrogen (N) and phosphorus (P) in the environment, leading to changes in the elemental stoichiometry of primary producers. These changes in elemental ratios may, in turn, alter the degree of stoichiometric mismatch between primary producer hosts and their pathogens. Here, we outline how ecological stoichiometry could be used as a framework to predict the effects of changing nutrient supply on stoichiometric mismatches in autotroph–pathogen interactions. We discuss empirical evidence linking pathogen performance to stoichiometric mismatches arising from shifts in elemental availability. Our synthesis indicates that fungi may be particularly sensitive to changes in N supply and viruses generally respond strongly to changes in the supply of either of these elements, but it also highlighted the need for additional data, especially for bacteria. Consequently, fungal pathogens may respond more strongly to changes in host C:N stoichiometry, whereas viruses may be highly sensitive to both changes in C:N and C:P of hosts. Additionally, our synthesis suggests that viruses may be more homeostatic than fungi, and therefore respond more strongly to changing elemental supplies. Revealing stoichiometric mismatches may greatly support our understanding of how host–pathogen interactions in primary producers will respond to changes in global biogeochemical cycles, controlling disease incidence in primary producers under scenarios of global change.